Diaminodicyanoquinones: Fluorescent Dyes with High Dipole Moments and Electron‐Acceptor Properties. Issue 24 (7th May 2019) - Rietsch, Philipp; Witte, Felix; Sobottka, Sebastian; Germer, Gregor; Krappe, Alexander; Güttler, Arne; Sarkar, Biprajit; Paulus, Beate; Resch‐Genger, Ute; Eigler, Siegfried
Abstract: Fluorescent dyes are applied in various fields of research, including solar cells and light‐emitting devices, and as reporters for assays and bioimaging studies. Fluorescent dyes with an added high dipole moment pave the way to nonlinear optics and polarity sensitivity. Redox activity makes it possible to switch the molecule's photophysical properties. Diaminodicyanoquinone derivatives possess high dipole moments, yet only low fluorescence quantum yields, and have therefore been neglected as fluorescent dyes. Here we investigate the fluorescence properties of diaminodicyanoquinones using a combined theoretical and experimental approach and derive molecules with a fluorescence quantum yield exceeding 90 %. The diaminodicyanoquinone core moiety provides chemical versatility and can be integrated into novel molecular architectures with unique photophysical features. Abstract : A light with a rotary switch : The fluorescence properties of diaminodicyanoquinones were studied by theoretical and experimental methods. Controlling the internal rotation around dihedral angle D β in diaminodicyanoquinones in the excited states determines the fluorescence quantum yield, which can exceed 90 %.